Electron-impact coherence parameters for 4(1)P(1) excitation of zinc - Piwinski, M.; Klosowski, L.; Chwirot, S.; Fursa, Dmitry; Bray, Igor; Das, T.; Srivastava, R. (Institute of Physics Publishing Ltd., 2018)
We present electron-impact coherence parameters (EICP) for electron-impact excitation of 41P1 state of zinc atoms for collision energies 40 eV and 60 eV. The experimental results are presented together with convergent close-coupling and relativistic distorted-wave approximation theoretical predictions. The results are compared and discussed with EICP data for collision energies 80 eV and 100 eV.